The Remarkably Strong Arctic Stratospheric Polar Vortex of Winter 2020: Links to Record‐Breaking Arctic Oscillation and Ozone Loss. Issue 22 (9th November 2020) - Lawrence, Zachary D.; Perlwitz, Judith; Butler, Amy H.; Manney, Gloria L.; Newman, Paul A.; Lee, Simon H.; Nash, Eric R.
Abstract: The Northern Hemisphere (NH) polar winter stratosphere of 2019/2020 featured an exceptionally strong and cold stratospheric polar vortex. Wave activity from the troposphere during December–February was unusually low, which allowed the polar vortex to remain relatively undisturbed. Several transient wave pulses nonetheless served to help create a reflective configuration of the stratospheric circulation by disturbing the vortex in the upper stratosphere. Subsequently, multiple downward wave coupling events took place, which aided in dynamically cooling and strengthening the polar vortex. The persistent strength of the stratospheric polar vortex was accompanied by an unprecedentedly positive phase of the Arctic Oscillation in the troposphere during January–March, which was consistent with large portions of observed surface temperature and precipitation anomalies during the season. Similarly, conditions within the strong polar vortex were ripe for allowing substantial ozone loss: The undisturbed vortex was a strong transport barrier, and temperatures were low enough to form polar stratospheric clouds for over 4 months into late March. Total column ozone amounts in the NH polar cap decreased and were the lowest ever observed in the February–April period. The unique confluence of conditions and multiple broken records makes the 2019/2020 winter and early spring a particularly extreme example of two‐way coupling between the troposphere and stratosphere. Plain Language Summary: Wintertime westerly winds in the polar stratosphere (from ∼15–50 km), known as the stratospheric polar vortex, were extraordinarily strong during the Northern Hemisphere winter of 2019/2020. The exceptional strength of the stratospheric polar vortex had consequences for winter and early spring weather near the surface and for stratospheric ozone depletion. Typically atmospheric waves generated in the troposphere spread outward and upward into the stratosphere where they can disturb and weaken the polar vortex, but tropospheric wave activity was unusually weak during the 2019/2020 winter. In addition, an unusual configuration of the stratospheric polar vortex developed that reflected waves traveling upward from the troposphere back downward. These unique conditions allowed the vortex to remain strong and cold for several months. During January–March 2020, the strong stratospheric polar vortex was closely linked to a near‐surface circulation pattern that resembles the positive phase of the so‐called "Arctic Oscillation" (AO). This positive AO pattern was also of record strength and influenced the regional distributions of temperatures and precipitation during the late winter and early spring. Cold and stable conditions within the polar vortex also allowed strong ozone depletion to take place, leading to lower ozone levels than ever before seen above the Arctic in spring. Key Points: The Arctic stratospheric polar vortex during the 2019/2020 winter was the strongest and most persistently cold in over 40 years Low tropospheric planetary wave driving and a wave‐reflecting configuration of the stratosphere supported the strong and cold polar vortex Seasonal records in the Arctic Oscillation and stratospheric ozone loss were related to the strong polar vortex